USE OF INTERACTIVE DYNAMIC MODELS IN ILLUSTRATIVE DISPLAY OF DRAWINGS - Shonazarov Adhamjon Odiljonovich (Academia Science Repository, 2023)
The article describes the didactic possibilities of interactive dynamic models and methodological recommendations for their use in the educational process.